Transgenerational effects of ungulates and pre-dispersal seed predators on offspring success and resistance to herbivory - Aguirrebengoa, Martin (PLoS One, 2018)
Herbivorous mammals and insect pre-dispersal seed predators are two types of herbivores that, despite their functional and morphological differences, tend to severely impact many plant species, highly decreasing their seed production and even imperiling the performance of their offspring through transgenerational effects. However, how they influence offspring resistance to herbivory remains largely unknown. In this study we experimentally examined the effects of ungulates and pre-dispersal seed predators on seed quality as well as on the emergence, survival and resistance to herbivory of the seedlings of a semiarid herb. We found that ungulates reduced seedling recruitment but increased seedling resistance to leaf miners. These effects were probably a consequence of insufficient carbon provisioning in seeds that reduced seed viability and provoked carbon limitation in seedlings. Pre-dispersal seed predators did not influence seedling recruitment, but seedlings from mothers damaged by ungulates and by pre-dispersal seed predators suffered less herbivory by grasshoppers. Remarkably, intra-individual differences in damage by pre-dispersal seed predators affected the rate of damage underwent by seedlings. That is, seedlings derived from fruits attacked by seed predators were more resistant to herbivores than siblings derived from un-attacked fruits in plant populations exposed to ungulates. To our knowledge, this is the first study reporting variation in transgenerational-induced resistance of seedlings from the same maternal plant. This study is a valuable contribution to the understanding of transgenerational effects of multiple herbivores and their implications for a deeper comprehension of the natural systems in which they co-occur.